Retouching scientific photography – the glass plate negatives collection at the Natural History and Science Museum – University of Porto - Pereira, Catarina (2018)
This work presents a part of a research project on retouching gelatin glass plate photographic negatives, its intentions, impact of the practice on the image and object and its current state of conservation. This is a case study on the use of retouching techniques on a scientific collection belonging to the former Dr. Mendes Correia Anthropology Institute, of the Natural History and Science Museum - University of Porto (MHNC-UP). In scientific photography there is a need for a rigorous record and true representation, which sets apart this type of photographic collection from others. Any alterations, such as retouching, should therefore have little or none aesthetic intentions. Retouched negatives were identified in this scientific and academic collection, and allowed to ascertain the purpose of their use and support the need for its preservation.